The Influence of Halal Awareness, Sustainable Lifestyle, and Digital Marketing on Halal Product Purchase Decisions among Generation Z - Irwan Moridu (Pt. Anagata Sembagi Education, 2026)
Generation Z has emerged as a religiously conscious yet digitally saturated consumer cohort in Muslim-majority markets, making halal purchase behavior a strategic concern for producers, marketers, and regulators. This study examines the influence of halal awareness, sustainable lifestyle, and digital marketing on halal product purchase decisions among Generation Z. While prior research has separately examined halal awareness, sustainability orientation, and digital marketing as antecedents of purchase behavior, few studies integrate these three constructs within one explanatory framework specific to Generation Z, and fewer address how sustainability values interact with religious motivation in a digitally mediated marketplace. This gap constitutes the novelty of the present study. Using a quantitative approach with a purposive sample of Generation Z consumers and Partial Least Squares Structural Equation Modeling (PLS-SEM), this study proposes and tests a conceptual model linking the three variables to purchase decisions. For illustrative purposes, hypothetical outcomes indicate that halal awareness exerts the strongest influence, followed by digital marketing and sustainable lifestyle, with all three variables jointly explaining a substantial proportion of variance in purchase decisions. The findings offer theoretical contribution to consumer behavior literature and practical implications for halal industry stakeholders designing religiously congruent, sustainability-oriented, and digitally optimized strategies for younger Muslim consumers